PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL TIJILI BENOA - Ni Luh Putu Pramudya Atma Jayanthi; A.A Ketut Sri Asih; NLK Julyanti Paramita Sari (Universitas Triatma Mulya, 2023)
The Effect of Work Environment and Work Discipline on Employee Performance at Tijili Benoa Hotel was investigated. The study utilized all 62 members of the population or all employees at Tijili Benoa Hotel as a sample. Participants were surveyed with forms and questionnaires, and data were gathered through documentation. Data analysis was performed using multiple linear regression analysis. The results of this analysis gave us two variables: X1 and X2. The regression equation model Y= 2,356+0,101X1+0,786X2 shows that the work environment, or X1, has a positive and significant effect on employee performance. This is shown in the regression coefficient b1 X1, which is equal to 0.101 with a 5% significance level. 66% of Employee Performance at Tijili Benoa Hotel is attributed to Work Environment and Work Discipline. The other 34% is explained by other variables not examined in this study. When examining the effect of X2 on Y, we see a positive regression coefficient b2 of 0.786 with a significance level lower than 0.05..